Corrosion behaviour in saline solution of pulsed‐electrodeposited zinc‐nickel‐ceria nanocomposite coatings. Issue 10 (17th August 2017) - Exbrayat, L.; Rébéré, C.; Ndong Eyame, R.; Steyer, P.; Creus, J.
Abstract : Pure Zn‐Ni and Zn–Ni–ceria (CeO2 ) nanocomposite coatings were deposited onto steel substrates using pulse electrodeposition process from an acidic bath combined with preliminary sonication. Influences of different parameters such as pulse parameters, addition of nanoparticles in the electroplating bath, use of sonication to ensure their dispersion, were studied in terms of morphology, composition, and corrosion behaviour in saline solution. Results revealed a strong influence of the electrodeposition parameters on the corrosion behaviour of the Zn‐Ni coatings. Incorporation of ceria nanoparticles is enhanced for the very short duration of the pulse due to the refinement of the microstructure. It was proved that composite coatings present an enhanced corrosion behaviour, while sonification does not afford a further improvement. Abstract : Pure Zn‐Ni and Zn–Ni–ceria nanocomposite coatings were deposited onto steel substrates using pulse electrodeposition process from an acidic bath combined with preliminary sonication. Influences of pulse parameters, addition of nanoparticles in the electroplating bath, use of sonication to ensure their dispersion, were studied in terms of morphology, composition and corrosion behaviour in saline solution.